2021
DOI: 10.1021/jacs.1c05387
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Free Bond Activation by Carboranyl Diphosphines

Abstract: We report metal-free bond activation by the carboranyl diphosphine 1-PtBu2-2-PiPr2-C2B10H10. This main group element system contains basic binding sites and possesses the ability to cycle through two-electron redox states. The reported reactions with selected main group hydrides and alcohols occur via the formal oxidation of the phosphine groups and concomitant reduction of the boron cage. These transformations, which are driven by the cooperation between the electron-donating exohedral substituents and the el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…Importantly, the observed reactivity is completely analogous to our recently reported examples of bond-activation of main group hydrides and alcohols by 1, which also led to the formation of zwitterions with two phosphonium centers and a dianionic cluster. 26 The synthesis of 2−5 features regioselective metal-free B−H bond activation with the formation of a direct C−B bond. Notably, the carborane cluster retained all its 12 vertices and was converted to its C 2 -symmetric nido-form through two-electron reduction.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Importantly, the observed reactivity is completely analogous to our recently reported examples of bond-activation of main group hydrides and alcohols by 1, which also led to the formation of zwitterions with two phosphonium centers and a dianionic cluster. 26 The synthesis of 2−5 features regioselective metal-free B−H bond activation with the formation of a direct C−B bond. Notably, the carborane cluster retained all its 12 vertices and was converted to its C 2 -symmetric nido-form through two-electron reduction.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…37 Notably, we have previously demonstrated such reoxidation for the isostructural nido-cluster of the chemically reduced dianionic 1 2− with [FeCp 2 ]PF 6 , which could be conveniently monitored by 31 P NMR spectroscopy, as the dianionic open-cage cluster exhibited two singlets in the spectrum, and the neutral closed-cage featured two doublets due to 31 P-31 P coupling. 26 The reaction of 2 and 2 equiv of [FeCp 2 ]PF 6 in tetrahydrofuran led to a mixture of products, with the predominant component possessing two singlet signals in the 31 P NMR spectra at 30.4 and 71.8 ppm, indicating the absence of coupling between phosphorus centers. A single crystal X-ray diffraction study revealed the structure of zwitterionic P( i Pr 2 )P(CHCPh)( t Bu 2 )(C 2 B 10 H 10 ) 6 (Figure 3).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The functionalization can be achieved at various vertices, particularly at acidic C­(1,2) positions. 1,2-Dichalcogenolato- o -carborane, 1,2-diphosphino- o -carborane, and 1,2-disila- o -carborane have been developed and extensively studied . We have reported the facile synthesis and functionalization of diamino o -carborane (Chart ).…”
Section: Introductionmentioning
confidence: 99%